Developing self-guided scuba dive routes in the Algarve (Portugal) and analysing visitors' perceptions - Rangel, M. O.
Scuba diving allows for underwater visitation of cultural and natural resources. Underwater routes can be used as a tool for guided and supervised underwater visits. Two scuba diving routes were implemented in the Algarve (South of Portugal), the "B24" and "Poço" diving sites. The perceptions of scuba divers regarding several aspects of the routes and the existing support infrastructures were studied following a survey carried out through face-to-face interviews from 2008 to 2012. Divers profile and their perceptions were analysed using 246 valid questionnaires. Divers were mainly Portuguese, over 30 years old and with more than 12 years of formal education. Some of the support infrastructures did not achieve a "good" or "acceptable" grade. This should be carefully considered by diving operators and managers, because perceptions tend to circulate throughout the diving tourists. All features of interpretative slates were graded as highly satisfactory. Overall, diver satisfaction increased slightly after route implementation, with an average ranking of "good". These findings support the implementation of underwater routes as a way to promote diving activity, and to increase divers' environmental education and awareness.